STERILIZABLE MINIATURE BIOREACTOR PLATFORM FOR ANAEROBIC FERMENTATION PROCESS - Arriafdi, Zainuddin; Ramachendrin, Arvind; Zainal Alam, Muhd Nazrul Hisham (Malaysian Journal of Science, 2021)
This paper presents the establishment of a miniature bioreactor platform for anaerobic microbial fermentation processes. It is made from a universal glass bottle and has a working volume of 16 mL. Reactor features included mixing via magnetic stirrer, temperature control via electrical heater and cells optical density (OD) sensing. All sensors and actuators integrated into the reactor were operated using LabVIEWTM (National Instrument, TX, US). The top lid of the bottle was modified to include a 3mm poly(methylmethacrylate) (PMMA) polymer layer where it was machined to provide spaces for fluidic ports and integration of sensors. Each reactor components were sterilized prior to conducting fermentation experiments. Main body of the reactor was made of glass and it was sterilized using the standard heat sterilization method (121oC for 15 minutes) where else other components were sterilized by exposure to UV light for 2 hours. A series of anaerobic fermentation experiments were conducted in batch mode using S.cerevisiae to evaluate the workability of the system. Fermentation experiments were conducted using inoculum concentration of 2 g∙L-1 and starting glucose concentration between 10 g∙L-1 and 20 g∙L-1. In every experiment, mixing was set to operate at 400 rpm and temperature was adjusted to 30 ± 2oC. Experiments were carried out until stationary phase was attained. Under these conditions, the best fermentation profile was obtained with glucose concentration of 20 /L where cell specific growth rate was found to be about 0.28 h-1. Bench marking step was also performed where results attained in a miniature bioreactor platform were comparable with the one attained using a 50 mL flask.